Refining employee treatment: Effects of government arrears repayment in China - Yanan Wang; Shuai Wang; Dongmin Kong; Cheng Xue (China Journal of Accounting Research)
Research on government procurement emphasizes its positive impacts, while paying insufficient attention to the risks posed by government arrears. We show that the implementation of China’s Special Supervision Action for Repaying Government Arrears significantly enhances employee treatment, particularly safety management and employee incentives, through monetary compensation, welfare, social security expenditure and investment in skilled human capital. The Special Supervision Action improves employee treatment by alleviating liquidity constraints and enhancing CEO confidence, which in turn boost firm productivity and performance. Cross-sectional tests indicate that the number of nearby bank branches, political connections, financial health, demand for human capital and external job opportunities affect these relationships. Our findings highlight the influence of government arrears repayment on corporate human capital investment.